Prosumption of Discourse of a ‘Beautiful Policewoman’ By Netizens in Online News Portal - Yustiwi, Gisela Ayu Hestuning (KnE Social Sciences, 2019)
The emergence of young and stylish policewomen called “beautiful policewomen” as newscasters in the traffic information broadcasting program and various events contribute to mass media coverage of policewomen. In February-March 2016 two online mass media in Indonesia, Liputan6 and Tribunnews, intensively reported a beautiful policewoman who worked as a secretary of West Java Police chief and involved in the handling of bomb incident operation in Bandung, West Java. The news discursively figure a professional woman in the masculine work field. Most of the news about “beautiful policewomen” mainly focused on their physical attractiveness and explored private issues. Such news had gone viral due to the content distribution through Facebook and gained various comments from netizens. This research focuses on the netizens’ comments on the news of “beautiful policewomen” on Liputan6 and Tribunnews, which had gone viral on Facebook. It is aimed to examine the prosumption of discourse of a “beautiful policewoman” by netizens. Using Gunther Kress’ multimodal critical discourse analysis, this research analyzes the forms of discourse of the related news contents and the way in which netizens discursively construct a policewoman as a subject. The research reveals that netizens tend to associate beauty with capability and physical attractiveness. On the other hand, the studied comments figure the prevalent masculine dominance in Indonesian police institution. The roles of professional women remain being overlooked not merely in the workplace such as police institution but also publicly by media as well as netizens. Keywords: online news; prosumption ; multimodal discourse ; policewoman;